Thyroid Dysfunction in Iraqi Patients with Acromegaly (Medico Legal Update, 2020)
Acromegaly is a chronic endocrine disorder caused by hypersecretion of growth hormone (GH) mostly because of pituitary adenoma. GH induces the formation of Insulin like Growth Factor1 (IGF1)from the liver. Both GH andIGF1 lead to sign and symptom of acromegaly.Aim: This study designed to identify the prevalence of thyroid dysfunction in Iraqi patients with acromegaly ,to identify the factors responsible for thyroid dysfunction in patients with acromegaly.Is the treatment modalities for acromegaly has a role in thyroid dysfunction?Study design: A cross sectional case control studyPatients and Method: seventy patients with acromegaly were enrolled from 2 different tertiary centers of endocrinology from Jan. -Dec. 2017 compared with 70 non acromeglic subjects. Their mean age 46 +/-11 years ;forty one (58.5%) males and 29(41.5%)females. Thyroid function test conducted to both patients and control groups including TSH, free T4 and total T3 in both centers. In addition to other variables.Results: Out of 70 (100%) patients with acromegaly; (51.5%) were euthyroid, (20%) had primary hypothyroidism , (15.7%)had central hypothyroidism and (12.8%) had hyperthyroidism that is significantly higher than normal population (p